The sources of income inequality in Indonesia: A regression-based inequality decomposition - Eko Wicaksono; Hidayat Amir; Anda Nugroho (Asian Development Bank Institute (ADBI), 2017)
Growing inequality is one important problem for a developing country, and Indonesia is no exception. Narrowing the gap between those at the top and the bottom of income distribution has become one of the government's main concerns. To achieve this goal, the sources of income inequality must be identified appropriately. Given the availability of household level data in Indonesia (Indonesia Family Life Survey), we are motivated to investigate the source of income inequality in Indonesia. The approach employed in this study is regression-based inequality decomposition using the Shapley value decomposition framework. The results show that education, wealth, as well as the employment sector are significant contributors to income inequality in Indonesia. These findings suggest that any policy aimed at reducing unequal access to education and finance is important to improve income inequality in the future.
Keywords: D31; D63; O53; 330; Economics; Education; Poverty; Indonesia